The Titanic secret : an Isaac Bell adventure - Cussler, Clive; Du Brul, Jack B (Cussler, Clive. Isaac Bell novels, 2019)
"When Isaac Bell attempts to decipher the forbidding deaths of nine men, he encounters a secret so powerful it could dictate the fate of the world in this riveting thriller by the #1 New York Times-bestselling author"--